Emergency E-learning and Teaching Practices in Algerian Universities During the Pandemic - SouameS, chahrazed (El Omda in Linguistics and Discourse Analysis, 2023)
The COVID-19 pandemic that affected the world forced the academic community to adopt preventive measures and implement new teaching methods in order to curb the spread of the virus. The shift from traditional classroom teaching to distance learning significantly disrupted the habits and practices of both teachers and students. This study focuses on the didactic and pedagogical adaptations implemented in Algerian universities during the COVID-19 health crisis. The collected data reveal that the challenges encountered did not hinder this mandatory transition to e-learning.